Akram between present and future. Academic success and socio-educational expectations - Rodorigo, Monia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
From a naturalistic approach, in this paper, we use the ethnographic method to delve into the academic transitions that immigrant students go through, and especially Akram, an 11-year-old immigrant boy who attends the last primary schools’ course at a “Calé’s school”. We do so to: a) describe characteristics of pedagogical variables that influence or may influence the day-to-day school life; b) analyse the moment of the academic transition and their impressions; c) deep on the influence of other variables (social, psychological, cultural, etc.) in the creation of socio-educational expectations.